Energy Efficiency and Industrial Competitiveness: Case Study of the GCC Region Using CS-ARDL and PMG-ARDL Approach - Sallam, Mohamed A. M.; Sadraoui, Tarek (International Journal of Energy Economics and Policy, 2025)
This study examines the relationship between industrial competitiveness and energy efficiency in the Gulf Cooperation Council (GCC) countries, whose economic development has historically relied on energy-intensive industries. With the global economy shifting towards energy-efficient and sustainable production, improving energy efficiency is a key driver of industrial competitiveness. Using panel data analysis over 1990-2024, we establish the impacts of decreases in energy intensity, the use of renewable energy, and policy interventions on industrial performance. Applying a comparative panel autoregressive distributed lag (CS-ARDL), NARDL, PMG-ARDL approaches, our results show that enhanced energy efficiency enhances industrial competitiveness by reducing production costs and increasing productivity. The impact, however, varies by industry, with industries using more energy incurring greater adaptation costs. The research provides useful insights to policy-makers on balancing economic diversification, energy reforms, and industrial sustainability to make the GCC competitive in the international market.